2011
DOI: 10.1074/jbc.m110.190637
|View full text |Cite
|
Sign up to set email alerts
|

Heterocomplexes of Mannose-binding Lectin and the Pentraxins PTX3 or Serum Amyloid P Component Trigger Cross-activation of the Complement System

Abstract: The long pentraxin 3 (PTX3), serum amyloid P component (SAP), and C-reactive protein belong to the pentraxin family of pattern recognition molecules involved in tissue homeostasis and innate immunity. They interact with C1q from the classical complement pathway. Whether this also occurs via the analogous mannose-binding lectin (MBL) from the lectin complement pathway is unknown. Thus, we investigated the possible interaction between MBL and the pentraxins. We report that MBL bound PTX3 and SAP partly via its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 44 publications
(63 reference statements)
4
125
1
Order By: Relevance
“…The molecular and functional characterization of the PTX3-Mficolin interaction described in this study lends further support to the integrated view of humoral innate immunity that emerged recently, according to which different pattern-recognition receptors collaborate in the activation and regulation of protective immune responses (3,(28)(29)(30). Cross talks between members of the defense collagens and pentraxins families are expected to broaden the individual recognition spectrum of these receptors for endogenous and exogenous danger signals and provide synergy in antimicrobial defense and/or maintenance of immune tolerance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The molecular and functional characterization of the PTX3-Mficolin interaction described in this study lends further support to the integrated view of humoral innate immunity that emerged recently, according to which different pattern-recognition receptors collaborate in the activation and regulation of protective immune responses (3,(28)(29)(30). Cross talks between members of the defense collagens and pentraxins families are expected to broaden the individual recognition spectrum of these receptors for endogenous and exogenous danger signals and provide synergy in antimicrobial defense and/or maintenance of immune tolerance.…”
Section: Discussionmentioning
confidence: 67%
“…With respect to the lectin complement pathway, CRP and PTX3 were shown to collaborate with L-ficolin for pathogen recognition and amplification of complement activation (10,28,29). Interaction between MBL and PTX3 was also recently reported to amplify complement activation through recruitment of C1q (30). However, direct ficolin-dependent activation of the lectin pathway by pentraxins has not been described so far (10,28,29).…”
mentioning
confidence: 98%
“…Complement C4b deposition was determined as previously described (7). In brief, A. fumigatus were incubated with rCL-12R&D (5 mg/ml) before addition of serum MBL2 (10%) as a complement source in the presence of TBS/Ca 2+ .…”
Section: Complement Activationmentioning
confidence: 99%
“…However, LP activation is primarily induced by collagen-like sPRMs, such as mannose-binding lectin (MBL) and the ficolins (5). It has also been shown that the CP and LP could be cross-activated through formation of heterocomplexes among PTX3, C1q, and the ficolins, as well as MBL (6,7). In contrast, the AP does not require Abs or sPRMs for its initiation, and it is often referred to as spontaneous and nondiscriminatory because it does not differentiate between self and nonself.…”
mentioning
confidence: 99%
“…Proteins were separated by 3-8% or 4-12% SDS-PAGE gel under reducing or nonreducing conditions according to the method of Laemmli (35) and visualized by immunoblotting or Coomassie brilliant blue, as described previously (29,36).…”
Section: Sds-page and Western Blotmentioning
confidence: 99%